2011
DOI: 10.1002/app.33596
|View full text |Cite
|
Sign up to set email alerts
|

On the characterization and spinning of an organic‐purified lignin toward the manufacture of low‐cost carbon fiber

Abstract: A Kraft hardwood lignin (HWL) and an organic-purified hardwood lignin (HWL-OP) were evaluated as potential precursors for the production of lowcost carbon fibers. It was found that the unpurified HWL exhibited poor spinnability while the HWL-OP exhibited excellent spinnability characteristics. Fibers of various diameters were obtained from the HWL-OP. Thermostabilization studies showed that oxidative stabilization can only be used to convert HWL-OP-based fibers into carbon fibers if extremely low heating rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
180
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(188 citation statements)
references
References 12 publications
5
180
1
2
Order By: Relevance
“…Different types of lignin precursors have been explored to produce carbon fibers, and most of these studies involved melt-spinning of a fusible lignin, which possessed a low enough softening temperature [4][5][6][7][8][9][10]. On the other hand, the normally low glass transition temperatures (Tg) of such lignin precursors required a slow heating rate to achieve crosslinking without fibers becoming tacky.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different types of lignin precursors have been explored to produce carbon fibers, and most of these studies involved melt-spinning of a fusible lignin, which possessed a low enough softening temperature [4][5][6][7][8][9][10]. On the other hand, the normally low glass transition temperatures (Tg) of such lignin precursors required a slow heating rate to achieve crosslinking without fibers becoming tacky.…”
Section: Introductionmentioning
confidence: 99%
“…A heating rate below 0.2 °C/min for Alcell lignin fibers was needed to prevent the fibers from fusing together [5]. Also, in a study reported by Baker et al, an organic purified lignin even required a heating rate as low as 0.01 °C/min to crosslink [9]. Organosolv lignin is readily processed compared with other lignin precursors due to its low Tg and stable melt viscosity imparted by substituents, but it lacks the ability to crosslink rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…36 Researchers are also investigating first spinning lignin-based fibers followed by carbonization to create single CNFs. 37 Lignin-based CNFs seem to be promising and may play a role in the lignin valorization needed to achieve economic selfsustainability in biorefineries.…”
Section: Wood-based Activated Carbon and Carbon Nanostructuresmentioning
confidence: 99%
“…In polymer blending systems, lignin generally increases the modulus and cold crystallization temperature, but it decreases the melt temperature (Doherty et al 2011). Recently, Baker et al (2012) developed kraft lignin-based CFs by using an organic solvent purification system applied to hardwood kraft lignins.…”
Section: Technical Lignins Are Divided Into Two Categories (El Mansoumentioning
confidence: 99%